"Sou analfabeta, mas não sou pacata": estratégias construídas por mulheres negras pouco escolarizadas para viverem em uma sociedade estruturada pela escrita - Ediany Aparecida Pereira Lima (2016)
This master's research aimed at understanding the strategies built by black women (black and brown) educandas of Youth and Adult Learning to live with little or no schooling in a society organized by the writing presence. For this, five women were selected - aged between 27 and 67 years - in literacy process in adult education. He attempted to rescue their life trajectories and work. And also raise the literacy events that these women participate in their daily lives to understand what such women find solutions to resolve situations that require reading and writing (in personal, professional and school). In addition, the objective was to identify "if" and "how" racial question appears in the speeches of these educandas. For this, it was used as a methodological procedure for qualitative research approach and as a tool the case study interviews, in two stages: in the first, the interviews were individual narratives and in the second, semi-structured interviews. The categories were articulated gender, race, job and generation and is used the social vulnerability concepts, strategy and illiteracy. It observed common paths between collaborators: abandonment, poverty, domestic violence, low wages, difficulties in taking as black women. All collaborators started on housework (whether paid or unpaid) in childhood, which is the main factor for switching or no access to school as children. It identified also a number of strategies created by these women to overcome the difficulties with reading and writing: speaking, use of memory, have people to support, product identification and tastes the colors, among others. It confirmed the initial hypothesis that the issues related to gender, race and little schooling combined produce social effects on the lives of these women. These effects were related to the integration into the labor market, income, schooling of children, access to health, consumption, etc. It is hoped that this work contribute increasing the knowledge about this public, so that the knowledge of their specific characteristics may contribute to the formation of educators for Adult Education, reversing into more appropriate pedagogical practices to their demands.